Basic strategies in women’s narrative, implemented in German and Russian fiction - Zubenko Я.В. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
The purpose of the current paper is to determine narrative strategies in women’s narrative based on the examples from two linguistic cultures – German and Russian. The article deals with the concepts of “female narrative” and “female narrator”. The study considered the texts of German and Russian female authors published at the beginning of the 21st century. Research methods included linguistic and cultural analysis, linguistic modeling and interpretation. The narrative strategies identified during the study were divided into I-I1 (strategies of self-presentation, introspection, retrospection, revision), I-THE OTHER (strategies of empathy and distance), I-YOU (suspense strategy). It was established that for representatives of German culture, relations between different generations influencing moral and cultural values of the family as a social institution are important, whereas for representatives of Russian linguistic culture accumulation of life experience, represented in the transfer of cultural values and traditions to subsequent generations, overcoming physical and moral difficulties, and searching reasons for failures in life from within are relevant.